Criminal Liability of Female Perpetrators of Sexual Harassment Against Minors - Isnawan, Fuadi (PDIH Untag Semarang, 2024)
This study aims to analyze the criminal liability of perpetrators of sexual harassment against dozens of male victims in Jambi City. The research method in this paper uses a normative juridical method that will examine the criminal liability of perpetrators of sexual harassment committed by women. In addition to this, it will also examine the role of psychiatric experts to determine the status of the ability to be responsible for the perpetrator of the crime. The results of this study indicate that it is necessary to fulfill several elements to say that the perpetrator is capable of being responsible according to the theory of criminal law and the Criminal Code. In addition, psychiatric experts play a role as expert testimony that can state whether the woman has a mental disorder or not because it is related to her ability to take responsibility. The researcher hopes that the paper can provide a better understanding of the criminal liability of female perpetrators of sexual abuse against underage boys and the role of psychiatric experts in these cases. The results of this research are expected to serve as a reference for law enforcement, child protection agencies, and the community in providing protection and justice for victims of sexual abuse, regardless of the gender of the perpetrator.